2011
DOI: 10.1111/j.1740-1461.2010.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Victim-Based Effects on Racially Disparate Sentencing in Ohio

Abstract: Scholars have argued that African-American men accused of violently victimizing whites receive especially harsh treatment in court. This thesis was tested with samples of felony defendants processed in Ohio courts before and after the implementation of sentencing guidelines. During the preguideline period only, African-American men accused of victimizing whites were less likely than other defendants to plead guilty in exchange for reduced charges and/or sentences, and African-American men incarcerated for viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Some studies demonstrate that early charging decisions affect final sentencing outcomes ( Wright and Engen 2006;Piehl and Bushway 2007;Shermer and Johnson 2010;Starr and Rehavi 2013). So do intermediate bail and pretrial detention decisions (Spohn 2009;Wooldredge et al 2011). However, only four studies address the issue of cumulative disparity.…”
Section: The Fifth Wavementioning
confidence: 99%
“…Some studies demonstrate that early charging decisions affect final sentencing outcomes ( Wright and Engen 2006;Piehl and Bushway 2007;Shermer and Johnson 2010;Starr and Rehavi 2013). So do intermediate bail and pretrial detention decisions (Spohn 2009;Wooldredge et al 2011). However, only four studies address the issue of cumulative disparity.…”
Section: The Fifth Wavementioning
confidence: 99%
“…These scholars have pointed out that focusing on a single decision‐making stage (i.e., sentencing) may mask disparities originating at other discretionary points in the system. Although select work demonstrated that early charging decisions (Piehl and Bushway, ; Shermer and Johnson, ; Wright and Engen, ) or intermediate bail and pretrial detention decisions (Spohn, ; Wooldredge et al., ) can affect final sentencing outcomes, only three studies addressed the issue of cumulative disparity in the prosecution and sentencing of criminal defendants (Schlesinger, ; Stolzenberg, D'Alessio and Eitle, ; Sutton, ). Each of these studies used different statistical techniques to analyze county‐level data from the State Court Processing Statistics series, and each of them reached somewhat different conclusions.…”
Section: Prior Research On Racial and Ethnic Disparity In Criminal Camentioning
confidence: 99%
“…These studies show the defendant's gender to be associated with case outcomes (including with the likelihood of being arrested)-with male defendants faring significantly worse than female 1 A "stereotype" is a culturally-based association between a concept (such as a social group) and an evaluative valence, either negative of positive (Kang et al 2012). defendants (Stolzenberg & D'Alession 2004;Starr 2015). Given equal crimes, women in the United States tend to receive shorter sentences than men, (Blume & Eisenberg 1999;Wooldredge et al 2011). If sentenced to death, women on death row are more likely than men to have their sentences commuted, or to otherwise be released from death row (Blume & Eisenberg 1999;Kraemer 2008).…”
Section: Gender-based Biases In Judicial Decisionsmentioning
confidence: 99%